2020
DOI: 10.1016/j.conbuildmat.2019.117174
|View full text |Cite
|
Sign up to set email alerts
|

Small to large strain mechanical behaviour of an alluvium stabilised with low carbon secondary minerals

Abstract: Deep dry soil mixing is a popular ground improvement technique used to strengthen soft compressible soils, with Portland cement being the most popular binder. However, its continued use is becoming less sustainable given the high CO2 emissions associated with its manufacture. Alkali-activated cements are considered to be viable low carbon alternative binders, which use industrial waste products such as blast furnace slag. This study focusses on the stabilisation of a potentially liquefiable soft alluvial soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…Chemical analysis of the clay showed high aluminium oxide (Al 2 O 3 ) and silicon dioxide (SiO 2 ) contents in a total mass of 96.73% (Table 3). Atterberg limits [33] Liquid limit 58% Plastic limit 15% Plasticity index 43% Specific gravity [34] G 2.57 The binder used to stabilise the clay is composed of two parts of ground granulated blast furnace slag (GGBS) and one part of sodium hydroxide (NaOH) in dosages of 5%, 10%, 12.5%, and 15% (by soil dry weight) and was developed by Sargent et al [26]. The blast furnace slags were supplied by Hanson Cements Ltd. in granulated form and are characterised by a density of 2.4-3 Mg/cm 3 at 20 • C and pH of 10-12 (DEV-S4-eluate according to EN 12457-4) (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical analysis of the clay showed high aluminium oxide (Al 2 O 3 ) and silicon dioxide (SiO 2 ) contents in a total mass of 96.73% (Table 3). Atterberg limits [33] Liquid limit 58% Plastic limit 15% Plasticity index 43% Specific gravity [34] G 2.57 The binder used to stabilise the clay is composed of two parts of ground granulated blast furnace slag (GGBS) and one part of sodium hydroxide (NaOH) in dosages of 5%, 10%, 12.5%, and 15% (by soil dry weight) and was developed by Sargent et al [26]. The blast furnace slags were supplied by Hanson Cements Ltd. in granulated form and are characterised by a density of 2.4-3 Mg/cm 3 at 20 • C and pH of 10-12 (DEV-S4-eluate according to EN 12457-4) (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…Increased normalised shear strength/stiffness and a tendency for dilation were also observed during the shear phase with increasing overconsolidation ratio (OCR). Sargent et al [26] reported higher values of maximum dilatation for an alluvial soil stabilised with alkali-activated blast furnace slag than those observed in reconstituted and undisturbed soil under the same confining stress. The authors associated this trend with the onset of softening behaviour caused by the breakdown of the cementitious bonding structure.…”
Section: Introductionmentioning
confidence: 95%
“…3 The fine-grained soil was stabilised with an alkali-activated binder composed by GGBS -NaOH (2 parts of GGBS -1 part of NaOH) at 7.5% dosage, in a concentration of 3.5 molal m. This binder was developed and tested by Sargent et al, 2016Sargent et al, , 2020aSargent et al, , 2020b, wherein the promising results with regards to the short term strength gains and also the enhanced geomechanical properties of the stabilised material, motivated its application in this study. The use of aluminosilicate sources with different amounts of Ca affects the rate of the gel formation, which requires longer curing periods to form in low Ca reaction products.…”
Section: Replacement Instruction: Replace Image Requestedmentioning
confidence: 99%
“…An abrupt strain softening behaviour after the peak stress was observed by Rios et al, 2018 in all cemented mixtures composed by lime and activated PFA with low Ca due to bonding degradations, with peak stresses at very low strain levels. Sargent et al, 2020b observed an undrained response characterized by work hardening up to peak conditions followed by strain softening in an alluvium soil stabilizedstabilised with activated blast furnace slags. In drained conditions, all specimens exhibited non-linear elastic work hardening behaviour up to peak strength, followed by strain softening.…”
Section: Introductionmentioning
confidence: 95%
“…limestone) for CEM-I production. GGBS and PFA-based AACM binders have been widely reported to successfully stabilise soft soils, producing geomechanical performances that are comparable or superior to CEM-I stabilised soils (Cristelo et al, 2013;Miranda et al, 2020;Sargent et al, 2020a;Sargent et al, 2020b;Consoli et al, 2021;Khanday et al, 2021).…”
Section: Introductionmentioning
confidence: 99%